Using Japanese pop cultural heritage to create a tourist product Exploring otaku tourism - Filipe Segurado Severino (Tourism)
The impact of Japanese pop culture on global tourism patterns is substantial, specifically in the promotion and growth of otaku tourism. Japan has become a hub for global tourists due to its ability to attract with the allure of interacting with the environments and storylines of their beloved pop culture media. This study examines the distinctive combination of traditional and contemporary cultural aspects, evaluating its influence on Japan’s tourism industry and on global perception. The economic and cultural benefits of using cultural exports to enhance the attractiveness of tourism are revealed through a literature review, with theoretical perspectives. This emphasizes the change in travel motivations towards genuine cultural experiences and the strategic significance of popular culture in promoting destinations. The findings indicate that Japan’s strategy of blending its abundant cultural heritage with modern cultural manifestations provides valuable lessons for other destinations seeking to attract tourists based on cultural identity. This movement highlights the capacity of cultural experience to influence tourism preferences, positioning Japan as a prominent illustration of how culture impacts international tourism dynamics.